Effect of different fermenting containers on the deterioration of Sichuan pickle. (August 2019) - Liu, Lei; She, Xiao; Qian, Yang; Li, Yalin; Tao, Yufei; Che, Zhenming; Liu, Guorong; Rao, Yu
Abstract: Sichuan pickles, the traditional Chinese fermented vegetables, are produced in a variety of containers during both the homemade and industrial processes. To ascertain the effect of the different containers on deterioration of the pickle, this study investigated the physicochemical properties, flavor characteristics and fungi diversity of pickles fermented in glass jars (GL), porcelain jars (PO) and plastic jars (PL) at the stage of deterioration. The results revealed that the contents of lactic acid and butyric acid in the pickles were higher in the PL than in the other jars on the 31st day of fermentation. Fermented radish presented the lowest hardness in the PL, while flavor compound identification suggested differences in the flavor profiles amongst the containers. At genus level, the abundance of Pichia and Candida, the top two predominating genera, were also higher in the PL than in the GL or PO. Meanwhile, pellicles formed mostly in the surface of brine in the PL. Correlation analysis uncovered the relevance between flavor compounds and fungi communities. These results suggested that pickle deteriorates to greatest extent in PL. This study provides new insights to the effect of containers on the deterioration of fermented pickle. Highlights: Containers made from glass, plastic and porcelain affect the deterioration of pickle. Pellicles formed mostly in the surface of brine in the plastic jars. Specific flavor substances in corresponding containers were identified. The abundance of Pichia and Candida were both the highest in the plastic jars. The coorelation between fungi and flavors were visualized by bioinformatic tools.